2012
DOI: 10.1186/1471-2164-13-583
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide association study for backfat thickness in Italian Large White pigs highlights new regions affecting fat deposition including neuronal genes

Abstract: BackgroundCarcass fatness is an important trait in most pig breeding programs. Following market requests, breeding plans for fresh pork consumption are usually designed to reduce carcass fat content and increase lean meat deposition. However, the Italian pig industry is mainly devoted to the production of Protected Designation of Origin dry cured hams: pigs are slaughtered at around 160 kg of live weight and the breeding goal aims at maintaining fat coverage, measured as backfat thickness to avoid excessive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 54 publications
12
93
2
Order By: Relevance
“…Excess marbling is another major cause of discard of hams from PDO consortia; a marbling score of 2 or more in the score system adopted in the present study is considered a defect by ham processors. In general, A and G yielded dressed hams with similar quality attributes and better processing ability than the other GGs, consistent with the breeding objectives of both GGs, which are aimed at maintaining fat coverage and improving raw ham traits related to the quality of dry-cured ham (Fontanesi et al, 2012;Cecchinato et al, 2008). The lower iodine number found in A-than in G-derived hams is consistent with their higher backfat carcass thickness, as carcass fatness represents a major source of variation in the lipid composition of pig carcasses (Lo Fiego et al, 2005).…”
Section: Ham Quality Traitssupporting
confidence: 74%
See 1 more Smart Citation
“…Excess marbling is another major cause of discard of hams from PDO consortia; a marbling score of 2 or more in the score system adopted in the present study is considered a defect by ham processors. In general, A and G yielded dressed hams with similar quality attributes and better processing ability than the other GGs, consistent with the breeding objectives of both GGs, which are aimed at maintaining fat coverage and improving raw ham traits related to the quality of dry-cured ham (Fontanesi et al, 2012;Cecchinato et al, 2008). The lower iodine number found in A-than in G-derived hams is consistent with their higher backfat carcass thickness, as carcass fatness represents a major source of variation in the lipid composition of pig carcasses (Lo Fiego et al, 2005).…”
Section: Ham Quality Traitssupporting
confidence: 74%
“…Four GGs were chosen on the basis of their distribution in commercial farms: a traditional cross between Italian Duroc boars and Italian Large White sows selected in the Italian Association of Pig Breeders' national breeding program (ANAS, A), and 3 commercial crosses obtained from DanBred Duroc (D), Goland C21 (G), or Topigs Tempo 40 (T) boars mated to sows of their parent sow lines. The A and G GGs are specifically intended for traditional heavy pig production and are genetically selected for carcass and ham quality traits (Fontanesi et al, 2012;Sturaro et al, 2008), while T is a Large White-derived line producing carcasses destined for the dry-cured ham industry (Morales et al, 2011).…”
Section: Pigs and Experimental Designmentioning
confidence: 99%
“…Studies of CasasCarrillo et al (1997) and Assis de Faria et al (2009) based on microsatellite analyses (including the IGF1 short tandem repeat marker) indicated that this chromosome region harbours QTL for growth and carcass traits. However, previous genome wide association studies we conducted on Italian Large White pigs by using single nucleotide polymorphisms in a few hundred candidate genes and the Illumina PorcineSNP60 BeadChip tool did not show any marker significantly associated with BFT in the region of SSC5 located around IGF1 (Fontanesi et al, 2012b(Fontanesi et al, , 2012c. These results would indicate that no important segregating SSC5QTL, at least for BFT, might be present in this breed.…”
Section: Association Analyses In Italian Large White and Italian Duromentioning
confidence: 58%
“…In addition, the simulated data mimicked the situation of a population in which genotyping just started for a limited number of generations, considering a limited budget that might be available at the beginning of genomic selection programs. The number of QTL in the genome and their effects were defined as prior information in simulating a real population, knowing that just a few important QTL for production traits segregate in heavy pig populations (Fontanesi et al, 2010(Fontanesi et al, , 2012(Fontanesi et al, and 2013. This prior information would affect results (Daetwyler et al, 2010), and in the present study it was decided to simulate a limited number of major QTL per chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Fontanesi et al, 2012). In the first run, for each heritability level, various assumptions on marker effect distributions and different SSTEP model parameters were tested (Tables 2 and 3) to retain a reduced number of possibilities in the following repetitions.…”
Section: Genomic Breeding Values (Gebv)mentioning
confidence: 99%